MENCARI JEJAK KONSEP JUDICIAL RESTRAINTDALAM PRAKTIK KEKUASAAN KEHAKIMAN DI INDONESIA - Wicaksono, Dian Agung; Tonralipu, Andi Sandi Antonius Tabusassa (Jurnal Hukum & Pembangunan, 2021)
The decision on judicial review of Laws by the Constitutional Court was allegedly not fully obeyed by the parties affected by the decision. One form of disobedience tothe judicial review decision by the Constitutional Courtwas shown by the Supreme Court concerning the decision related to the opening of the opportunity to submit a Peninjauan Kembali more than once, which was responded by the Supreme Court with internalregulations which emphasized that Peninjauan Kembali could only be done once.From the phenomenon, this research tries to trace the concept of judicial restraint in the practice of judicial power in Indonesia, as well as measuring the implementation and justification of the concept of judicial restraint in the practice of judicialpower in Indonesia. This is normative legal research that uses secondary data. The results indicate that the Supreme Court and the Constitutional Court are expected to have the awareness to apply judicial restraint in the exercise of judicial review authority.